Perancangan Sistem Informasi Akuntansi Pencatatan Simpan Pinjam - Arman Maulana (Universitas Koperasi Indonesia, 2022)
Cooperative is a legal entity established by an individual or a cooperative legal entity, with the separation of the members' assets which become the capital to run a business, which fulfills the common aspirations and needs in the economic, social and cultural fields in accordance with the values and principles of the cooperative. The savings and loan system that runs at Primkop Kartika Ardagusema still uses manual recording without using an information system. With human records, there are often errors in recording and the resulting reports are inaccurate. In order to improve service to members and overcome existing problems, a savings and loan information system is needed, an information system created using the waterfall method. And use netbeans for database storage. After conducting research on Primkop Kartika Ardagusema, it can be concluded that this cooperative still uses a manual system for its savings and loan transactions. This manual system does not support its operational activities. Errors during data processing still occur frequently. With this computerized system, it is hoped that it can solve previous problems and can produce more accurate reports so that service to members is better.